Implementasi Program Pusat Informasi Konseling Mahasiswa (PIK-M) BKKBN di Kota Palangka Raya - Nicodemus R Toun; Hayatun Nufus (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
This study aims to find out and describe the Implementation of the BKKBN Student Counseling Information Center (PIK-M) Program in the city of Palangka Raya. The type of research used is a qualitative method, by taking a sample of 4 (four) PIK-M from 8 (eight) PIK-M in the city of Palangka Raya. Namely, (1) PIK-M Barendeng (UNPAR), (2) PIK-M Fasko (UMP), (3) PIK-M Barigas (IAIN), (4) PIK M Bakti Husada (Poltekkes). Data collection techniques are documentation, observation, and interviews. The informants consisted of Head of KS / PK, Head of Sub-Division of BKR, Trustees, Managers, and members of each PHC-M. The cornerstone of theory in this research is implementation and program, where implementation is actions to achieve the objectives outlined in policy decisions. The program is as a unit or unit of activity which is the realization or implementation of policy takes place in a continuous process and occurs in an organization involving a group of people. According to G. Shabbir Cheema and Dennis a. Rondinelli has four factors that influence the implementation of policies or programs, namely: (a) environmental conditions, (b) relations between organizations, (c) organizational resources for program implementation, (d) characteristics and capabilities of implementing agents